What are the factors influencing Iran’s sports talent identification process? Findings of a qualitative study - Kalani, A.; Elahi, A.; Nasrollah-Sajjadi, S.; Zareian, H. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
This study aimed to determine the factors affecting the process of Iranian sport talent identification. Considering the exploratory nature of the subject, the qualitative research method and the theorizing approach based on the data were used. First, through the initial studies and the systematic review of related resources, the inventory of effective signs was identified. Subsequently, 23 targeted semi-structured interviews with experts were conducted through snowball method. The interviews continued to reach the theoretical saturation. The open coding results indicated that 145 primary signs and 57 final signs were extracted. In the axial coding, the final signs were classified into 18 concepts and 7 main categories. Consequently, the identified categories including environmental conditions, individual, cultural, and social issues, infrastructure, management system, participation in sports, and key stakeholders were determined. The country sports managers can use the identified concepts and categories for their future plans in order to develop talent identification.